Active physician attitude vs. patient inertia: detection of chronic myeloid leukemia during periodic examinations - Andrzej Marcinkiewicz (Nofer Institute of Occupational Medicine, 2022)
The case report concerns the prophylactic and medical certification procedure initiated during periodic examinations, which led to the early detection of chronic myeloid leukemia. Particular attention was paid to the shortening of the period of validity of the periodic examination, justified by an abnormal health condition that is not directly related to the working conditions, as well as the method of communication and influencing the employee to comply with medical recommendations. The conclusions stated that, although obligatory and periodic preventive examinations for the purposes of the Labor Code create the possibility of early detection of unawereness of disease, thus giving a chance to improve health, but at the same time they can be treated as an interference with the individual's right to self-determination about his life and health. It was noted that the key factor in assessing the situation would be the attitude of the occupational medicine physician and the manner of his communication with the employee, who would not be forced, but convinced - for his benefit, to undertake diagnostics or health interventions. Med Pr. 2022;73(6):485-90